Emotional reactivity, functioning, and C-reactive protein alterations in remitted bipolar patients: Clinical relevance of a dimensional approach. (August 2017) - Dargél, Aroldo A; Godin, Ophelia; Etain, Bruno; Hirakata, Vânia; Azorin, Jean-Michel; M'Bailara, Katia; Bellivier, Frank; Bougerol, Thierry; Kahn, Jean-Pierre; Passerieux, Christine; Aubin, Valerie; Courtet, Philippe; et al.
Objectives: Inter-episode mood instability has increasingly been considered in bipolar disorder. This study aimed to investigate emotional reactivity as a major dimension for better characterizing remitted bipolar patients with subthreshold mood symptoms and functional status. This study also aimed to investigate whether high-sensitivity C-reactive protein, a marker of low-grade inflammation, could be a biological marker of emotional dysregulation in bipolar disorder (BD). Methods: Cross-sectional study of 613 subjects who met Diagnostic and Statistical Manual of Mental Disorders–Fourth Edition criteria for BD recruited from the FondaMental Advanced Centers of Expertise in Bipolar Disorders cohort from 2009 to 2014. All patients had been in remission for at least 3 months before assessment. Patients were classified into three groups according to levels of emotional reactivity. Emotional reactivity was assessed by using the Multidimensional Assessment of Thymic States, and functional status was assessed by the Functioning Assessment Short Test. Clinical characteristics and blood sample were collected from all patients. Results: In total, 415 (68%) patients had abnormal emotional reactivity. Independent of potential confounders, including age, gender and subthreshold mood symptoms, serum levels of high-sensitivity C-reactive protein were significantly higher in patients with emotional hyper-reactivity (median = 4.0 mg/L, interquartile range = 2.7–5.6), and with emotional hypo-reactivity (median = 3.0 mg/L, interquartile range = 1–4) compared with patients with normal emotional reactivity (median = 0.95 mg/L, interquartile range = 0.4–1.9, p  < 0.001). Patients with emotional hyper-reactivity showed significant cognitive functioning impairment ( p  < 0.001). Conclusions: Emotional reactivity appears to be a relevant dimension for better characterizing remitted bipolar patients with subthreshold mood symptoms. Levels of high-sensitivity C-reactive protein may be an objective marker of emotional dysregulation in BD. Further studies are needed to confirm our findings.